Interlaminar and varicose-projection astrocytes: toward a new understanding of the primate brain - Ciani, Caterina; Falcone, Carmen (Frontiers in Cellular Neuroscience, 2024)
In the last years, science started to move toward a more glio-neurocentric view, in which astrocytes are hypothesized to be directly involved in cognitive functions. Indeed, astrocytes show a variety of shapes with species-specific characteristics, suggesting a specialization of roles during evolution. Interlaminar (ILA) and varicose-projection (VP-As) astrocytes show an anatomical organization that is different compared to the classical horizontal net typically formed by protoplasmic and fibrous astrocytes. ILAs show a modular architecture with the soma in the first cortical layer and processes toward the deep layers with species-specific length. VP-As reside in the deep layers of the cortex, are characterized by varicosities on the longest processes, and are individual-specific. These characteristics suggest roles that are more complex than what was theorized until now. Here, we recapitulate what we know so far from literature from the first time ILAs were described to the most recent discoveries, spanning from morphology description, hypothesis on the development to their features in diseases. For a complete glance on this topic, we included a final paragraph on which techniques and models were used to study ILAs and VP-As, and what new avenues may be opened thanks to more novel methods.